Practical positioning control of a one mass rotary system - Mohd Nor, Rozilawati (2015)
One mass rotary system, is a mechanism that commonly used in industries. Hence for this research, a robust and practical controller design for a one mass rotary system is discussed. The controller is designed and improved based on the conventional structure of the Nominal Characteristic Trajectory Following (NCTF) controller. The continuous motion NCTF (CM-NCTF) controller is proposed for a point to point (PTP) positioning system. The CM-NCTF controller comprising a nominal characteristic trajectory (NCT) and the proportional integral (PI) compensator element. It is designed without knowing the exact model and parameters of the system. The design procedure is applicable, easy to understand and has a simple controller structure. The NCT is constructed from open loop experiment responses while PI compensator is designed experimentally based on the system stability graph.The effectiveness of the proposed controller in positioning and tracking control performance is evaluated experimentally. The experiment was done using various input to examine the controller performance towards parameter variation. While, the controller robustness is evaluated by applying different load into the system to examine system sensitivity towards the disturbance. Then, the effect of positioning, tracking and robustness are compared to the PID and the conventional NCTF controllers. The CMNCTF controller demonstrates good positioning response by having less steady state error, shorter settling time and also small or zero overshoot in comparison to the PID controller. Besides, the CM-NCTF controller performs better tracking control performance when various input frequencies are applied to the system. The proposed controller is proved to have a good positioning, smoother tracking and less sensitivity towards the disturbance. In conclusion, the CM-NCTF controller is more accurate and robust than the PID controller.